Роль навчальної дисципліни «Трактори і автомобілі» у формуванні професійних компетенцій майбутнього фахівця аграрної сфери - Болтянський, Олег Володимирович; Болтянский, Олег Владимирович; Boltianskyi, Oleh; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia (My University, 2019)
UK: В статті розглянуто способи формування професійних компетенцій майбутнього фахівця аграрної сфери. EN: The article deals with ways of the formation of professional competences of the future specialist of agrarian sphere are considered.
The role of the academic discipline "Tractors and cars" in the formation of professional competencies of the future specialist of the agrarian sector
Keywords: навчальна дисципліна; компетенції; компетентність; компетентнісний підхід; фахівець-аграрій; academic discipline; competence; competency; competency approach; agrarian expert